Bιβλιοκρισία: R. G. OUSTERHOUT, Visualizing Community, Art, Material Culture and Settlement in Byzantine Cappadocia, Dumbarton Oaks Research Library and Collection, Dumbarton Oaks Series XLVI, Washington, D.C. 2017 - ΦΟΥΚΑΝΕΛΗ, Γεωργία (Byzantina Symmeikta, 2019)
Βιβλιοκρισία: RΟΒΕRΤ G. OUSTERHOUT, Visualizing Community, Art, Material Culture and Settlement in Byzantine Cappadocia, Dumbarton Oaks Research Library and Collection, Dumbarton Oaks Series XLVI, Washington, D.C. 2017, 532 σελ., 510 εικ., ISBN 9780884024132